Signs and Meanings In Rweinda’s Novel Antares (Charles Sanders Pierce Theory) - Novi Nuraini; Dessy Wardiah; Siti Rukiyah (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The purpose of this study is to describe the signs and meanings of icons, index, and symbols in the novel Antares by Rweinda in terms of semiotic studies. This research is a qualitative research with descriptive method. The data collection technique used documentation, and the validity of the data was carried out by triangulation techniques and the data were analyzed by content analysis techniques. The results showed that the signs and meanings in the novel Antares by Rweinda with a semiotic approach found as many as 231 quotations in the form of aspects of icon signs, indexes and symbols which are divided into several classifications of forms. There are 74 quote icons, namely (1) social marker icons with 13 quotes, (2) topology icons with 12 quotes, (3) metaphor icons with 27 quotes, and (4) onomotope icons with 22 quotes. Then found an index of 59 citations in the form of (1) behavior index with 36 citations, (2) performance index with 16 citations, (3) occupation index with 2 citations and, (4) lifestyle index with 5 citations. Then found as many as 98 symbols, namely (1) personal symbols totaling 62 quotes, (2) agreement symbols totaling 30 quotes and, (3) universal symbols totaling 6 quotes. Signs and meanings that were found the most were marks on personal symbols from 62 quotes. While the least found are index marks in the form of a job index as many as 2 citations.